Confounding compression: the effects of posture, sizing and garment type on measured interface pressure in sports compression clothing - Brophy-Williams, N.; Driller, M. W.; Shing, C. M.; Fell, J. W.; Halson, S. L. (Journal of Sports Sciences, 2015)
The purpose of this investigation was to measure the interface pressure exerted by lower body sports compression garments, in order to assess the effect of garment type, size and posture in athletes. Twelve national-level boxers were fitted with sports compression garments (tights and leggings), each in three different sizes (undersized, recommended size and oversized). Interface pressure was assessed across six landmarks on the lower limb (ranging from medial malleolus to upper thigh) as athletes assumed sitting, standing and supine postures. Sports compression leggings exerted a significantly higher mean pressure than sports compression tights (P < 0.001). Oversized tights applied significantly less pressure than manufacturer-recommended size or undersized tights (P < 0.001), yet no significant differences were apparent between different-sized leggings. Standing posture resulted in significantly higher mean pressure application than a seated posture for both tights and leggings (P < 0.001 and P = 0.002, respectively). Pressure was different across landmarks, with analyses revealing a pressure profile that was neither strictly graduated nor progressive in nature. The pressure applied by sports compression garments is significantly affected by garment type, size and posture assumed by the wearer.